The distinct biological role of JAML positions it as a promising target for treating human cancers and a range of other diseases - Dong, Zhilin; Liu, Ning; Sun, Meili (Frontiers in Immunology, 2025)
Junctional adhesion molecule-like protein (JAML), a member of the junctional adhesion molecule (JAM) family, is widely expressed in various cells. This review examines the progress made in understanding JAML, beginning with its discovery and subsequent characterization. It emphasizes the mechanisms through which JAML influences biological processes, including cell migration, inflammation, lipid metabolism, and antitumor immunity, as demonstrated by recent studies. In addition, the clinical relevance of JAML is analyzed in the context of diseases linked to these processes. Particular attention is given to the effects of JAML on tumor cell proliferation and migration, alongside its pivotal role in regulating lymphocyte infiltration into the tumor microenvironment. Collectively, The balance between JAML’s pro-inflammatory and anti-tumor functions underscores its therapeutic promise.